Primary Production, Community Respiration, and Net Community Production along Oxygen and Nutrient Gradients: Environmental Controls and Biogeochemical Feedbacks within and across “Marine Lakes” - Wilson, Jesse; Abboud, Sarah; Beman, J. Michael (Frontiers in Marine Science, 2017)
Declining ocean oxygen content driven by anthropogenic climate change has wide-ranging ramifications for marine ecosystems. These effects are significant but complex at the upper margins of expanding oxygen minimum zones (OMZs), where deoxygenation and biogeochemical feedbacks to low dissolved oxygen (DO) are regulated by biological production and consumption of DO via gross primary production (GPP) and community respiration (CR). We used ‘marine lakes’—bodies of seawater surrounded by land—as a natural experimental system for examining the environmental factors that dictate coupling and de-coupling between GPP and CR. Distinct gradients in DO (from fully oxygenated to anoxic conditions), temperature, light, quantity and quality of organic matter, presence of key nutrients, and microbial community structure occur across multiple stratified meromictic lakes and well-mixed holomictic marine lakes present in Palau. We found consistently high GPP rates in stratified meromictic lakes (>10 mmol O2 m-3 d-1)—especially near the chemocline, where nutrients diffuse upwards from anoxic waters—and a wider range of rates in well-mixed lakes (0.350 to 57.9 mmol O2 m-3 d-1). In contrast to GPP, CR rates were typically lower and less variable across different depths and lakes. Most depths in most lakes were therefore net autotrophic (i.e., net community production [NCP] > 0). However, experimental additions of ammonium (5 μM) and labile organic carbon (100 μM) had strong effects on CR, resulting in (i) several-fold increases in CR, (ii) larger increases in CR in meromictic lakes with chemoclines near the surface, and (iii) the occurrence of net heterotrophy and DO consumption. Our results are indicative of several biogeochemical feedback mechanisms to deoxygenation present at the upper margins of shoaling OMZs that are governed by nutrient turnover. In marine lakes, these feedbacks can have strong effects on nutrient uptake and the production and consumption of oxygen, with implications for carbon, nutrient, and oxygen cycling throughout large areas of the ocean.